PENGARUH MOTIVASI DAN VISI KERJA KARYAWAN SERTA KEGAGALAN KUALITAS PELAYANAN DI MASA LALU TERHADAP PENINGKATAN KUALITAS PELAYANAN PADA FAKULTAS EKONOMI UNIVERSITAS TRISAKTI JAKARTA - Yolanda Masnita Siagian; Puti Handayani (Universitas Trisakti, 2006)
This research observed Ihe influence of Motivation and Job Vision and Service Failure in the past towards the Enhancement of Service Quality on Eccnomic Faculy, Trisakti University, Jakarta. This research was implemented based on the previous research by Hays and Hill (2001). The research observes whether (motivation and employee's job vision and service failure in the past) individually and constinuously lowards service quality in the presentand also to observe whatsortof efforts thal could be implemented by Economics Faculty, Trisakti University, Jakarta in enhancing its service quality. Dala collecting was obtained by distributing questionnaire towards 380 students of Economic Faculy, Trisakti University, Jakarta on 3 (three) majors which are: Accounting, Management, Economics. Number of samples were determined by using Slovin formula, while the sample selecting was implemented by using convenience sampling technique. Data analysis method were used in this research was implemented through several test such as instrumenttest (validity and reliability), correlation test, determinant coefficient test, linear regression test, hypotheses tests (t-test and F-test) and also classical assumption test (multicolinerity, heteroskedacity, auto correlation tests). Software was used in processing data is program version 13. Hypotheses were used with the significance rate of 0.05 and the confidence level of 95% The result of the data analysis which was implemented by using several tests, showed that there is a significantinfluence of motivation and employee's job vision and service failure in the past towards the enhancement service quality in the present. The result showed that there is a significant influence between molivation and employee's job vision and servicefailure in the past continously lowards service quality in the present. In addition, in order to improve service quality in the environment, the writer has provided seven efforts that could be implemented by Economics Faculy, Trisakti University.